2016
DOI: 10.1007/s10529-016-2141-0
|View full text |Cite
|
Sign up to set email alerts
|

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos

Abstract: PCI-24781 improves nuclear reprogramming and the developmental potential of pig SCNT embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Accumulating evidence indicates that impaired nuclear epigenetic reprogramming, involving DNA methylation and histone modification, may be the leading source of aberrant epigenetic modification (Ohgane et al, ; Santos et al, ) and gene expression (Jiang et al, ; Zou et al, ) in cloned embryos. Indeed, numerous recent studies demonstrated the ability of HDACi to improve cloning efficiency, although the exact molecular mechanism underlying these benefits remains unknown (Jin et al, ,).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that impaired nuclear epigenetic reprogramming, involving DNA methylation and histone modification, may be the leading source of aberrant epigenetic modification (Ohgane et al, ; Santos et al, ) and gene expression (Jiang et al, ; Zou et al, ) in cloned embryos. Indeed, numerous recent studies demonstrated the ability of HDACi to improve cloning efficiency, although the exact molecular mechanism underlying these benefits remains unknown (Jin et al, ,).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear reprogramming process mainly involves epigenetic modifications, such as DNA methylation and histone acetylation, and phosphorylation, which may be a key factor in improving cloning efficiency (Su et al, ). Epigenetic reprogramming and SCNT cloning efficiency were recently enhanced using several epigenetic remodeling agents, such as the DNA methylation inhibitors 5‐aza‐2′‐deoxycytidine (Huan et al, ) and RG108 (Sun et al, ) or histone deacetylase inhibitors (HDACi) valproic acid (Kang et al, ; Miyoshi et al, ), trichostatin A (Chen et al, ), Scriptaid (Liang, Zhao, Choi, Kim, & Cui, ; Whitworth, Zhao, Spate, Li, & Prather, ), MGCD0103 (Jin et al, ), and PCI‐24781 (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, those epigenetic modifiers represent not only the subclass of highly specific extrinsic HMT inhibitors (HMTi) such as G9A (H3K9) HMTi, whose pivotal member is diazepin‐quinazolin‐amine derivative termed BIX‐01294 (Cao et al, ; Huang et al, ), but also the subclass of ectopic non‐specific DNMT inhibitors, whose most important members are: (a) 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, , ; Ning et al, ); and (b) zebularine (a nucleoside analog of cytidine; Diao et al, ). On the other hand, they represent the subclass of ectopic non‐selective HDAC inhibitors (HDACi), whose main members are (a) TSA (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, ; Opiela et al, ; Samiec et al, ); (b) scriptaid (SCPT) (Liang, Zhao, Choi, Kim, & Cui, ; Xu et al, ; Zhang et al, ); (c) oxamflatin (Hou et al, ; Mao et al, ); (d) sodium butyrate (NaBu) (Kumar et al, ; Liu et al, ); (e) m ‐carboxycinnamic acid bis hydroxamide (CBHA) (Song et al, ); (f) panobinostat, also known as LBH589 (Jin et al, ); (g) abexinostat, also termed PCI‐24781 (Jin et al, ); (h) quisinostat, also called JNJ‐26481585 (Jin, Guo, et al, ); and (i) dacinostat, also named as LAQ824 (Jin, Lee, Taweechaipaisankul, Kim, & Lee, ). The initiation of chromatin decondensation and gene transcriptional activity is triggered both via highly specific and transient inactivation of G9A (H3K9) HMTs by BIX‐01294 (Cao et al, ; Huang et al, ) and via non‐specifically blocking the biocatalytic activity of either DNMTs by 5‐aza‐dC and zebularine (Diao et al, ; Saini et al, ) or HDACs by TSA, SCPT, oxamflatin, NaBu, CBHA, panobinostat, abexinostat, quisinostat and dacinostat (Jin, Lee, et al, ; Jin et al, , ; Jin, Guo, et al, ; Kumar et al, ; Song et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they represent the subclass of ectopic non-selective HDAC inhibitors (HDACi), whose main members are (a) TSA (Huan, Wang, et al, 2015;Huan et al, 2014;Opiela et al, 2017;Samiec et al, 2015); (b) scriptaid (SCPT) (Liang, Zhao, Choi, Kim, & Cui, 2015;Xu et al, 2013;Zhang et al, 2017); (c) oxamflatin (Hou et al, 2014;Mao et al, 2015); (d) sodium butyrate (NaBu) (Kumar et al, 2013;Liu et al, 2012); (e) m-carboxycinnamic acid bishydroxamide (CBHA) (Song et al, 2014); (f) panobinostat, also known as LBH589 ; (g) abexinostat, also termed PCI-24781 (Jin et al, 2016); (h) quisinostat, also called JNJ-26481585 (Jin, Guo, et al, 2017); and (i) dacinostat, also named as LAQ824 (Jin, Lee, Taweechaipaisankul, Kim, & Lee, 2017). The initiation of chromatin decondensation and gene transcriptional activity is triggered both via highly specific and transient inactivation of G9A (H3K9) HMTs by BIX-01294 (Cao et al, 2017;Huang et al, 2016) and via non-specifically blocking the biocatalytic activity of either DNMTs by 5-aza-dC and zebularine (Diao et al, 2013;Saini et al, 2017) 2017; Jin et al, 2013Jin et al, , 2016Jin, Guo, et al, 2017;Kumar et al, 2013;Song et al, 2014;Zhang et al, 2017). Such epigenomic modulation of nuclear donor cells, nuclear recipient cells and/or SCNT-derived embryos appears to enhance the reprogrammability of donor cell nuclei that have been transferred into a host cytoplasm of enucleated oocytes.…”
mentioning
confidence: 99%
“…Recently, there were several reports that HDACi treatment positively regulates histone acetylation levels, epigenetic reprogramming, gene expression, full term embryo development and DNA methylation levels in a manner similar to these events taking place in in vitro fertilized embryos. The development of porcine SCNT embryos was improved by treatment with HDACi, such as trichostatin A (TSA) [10, 11], valproic acid (VPA) [12], scriptaid [13, 14], oxamflatin [15], sodium butyrate (NaBu) [16], LBH589 [17], CUDC-101 [18], m-carboxycinnamic acid bishydroxamide (CBHA) [3], PXD101 [19], suberoylanilide hydroxamic acid (SAHA) [20] and PCI-24781 [21]. …”
Section: Introductionmentioning
confidence: 99%